Analysis of the main labor problems faced by human capital within the marble factories of Tepexi de Rodríguez, Puebla - Guevara, Miguel Ángel Luna; Tovar, Edgardo Roldán y; Olmos, Claudia Domínguez; Regules, Behetzaida Martínez (Seven Editora, 2024)
According to the General Directorate of Mining Development (2015), the antecedents of the exploitation of marble in Mexico date back to the last years of the Porfirista period (1876-1911), particularly in the last two decades of the nineteenth century and in the first years of the twentieth century, there was a growth of the most representative cities around the world.  with the consequent dynamism of the demand for construction materials, as well as industrial metals. In this context, some businessmen showed interest in taking advantage of this conjunctural moment, investing resources in our country in the exploitation, not only of traditional minerals such as gold, silver or copper, but also of other minerals that were in growing demand, among which was marble. Valles and Márquez (2004) state that the discovery of the marble in Tepexi de Rodríguez occurred during the construction of the highway in 1963 when General Antonio Nava Castillo was Governor of the State of Puebla. The extraction of marble began around 1964, based on the use of pickaxe, bar, spikes, train ladder jacks, and marro. According to Ros (2016), in the marble sector there are several labor problems that affect human capital. These issues can have a significant impact on worker productivity and well-being. The study carried out was of a mixed type with the purpose of analyzing the main labor problems faced by human capital within the marble factories of Tepexi de Rodríguez, Puebla, in order to define the current factors that affect the human capital in the work that is carried out in the marble industry of this locality, having an exploratory-descriptive scope.  through a case study of a company located in that place, which began operations in 1970, taking a sample of 206 employees who worked in it. As identified in the study, the human capital within the analyzed company faces several problems that limit their labor well-being, it was also identified that there are still bad practices in the management of Human Capital, as well as the lack of training that is an important aspect in any industry or company. In addition, it should be noted that three of the main problems faced by human capital according to the mentions made by workers, firstly, are poor salaries and lack of benefits, secondly, health because there are no long-term disease prevention programs, and thirdly, the lack of occupational safety since there are no hygiene and safety programs that allow them to prevent latent risks throughout the country. the processing of marble. DOI:https://doi.org/10.56238/sevened2024.010-017